A Currency Crises Model That Works: A Payments Disequilibrium Approach - Ekniti Nitithanprapas; Thomas D. Willett (Claremont McKenna College, Department of Economics, 2000)
The rash of international financial crises in the 1990s have stimulated great interest in models to predict crises and explain the patterns of contagion that follow crisis. In both of these respects analysis of the Asian crisis has proven to be quite controversial. While some economists have argued that the Thai crises should have been quite predictable based on the similarities between Thailand's situation and that of the Mexican crisis two years prior, see, for example, Salvatore (1999), other economists have argued that the Thai crisis was not predictable on the basis of the then available research, see, for example, Furman and Stiglitz (1998). Likewise some leading economists have argued that the pattern of contagion following the Thai crisis cannot be explained by rational economic models.1 As a consequence they point to self-fulfilling and/or destabilizing speculation, rather than economic fundamental as the primary causes of the Thai crisis and subsequent international financial contagion.
Keywords: 330